Triton X-114 and Amine-Based Wash Strategy Reduces Lipopolysaccharides to FDA Limit and Achieves Purer, More Potent Recombinant Immunotoxin - George, Rebekka; Gsottberger, Franziska; Ammon, Anna-Maria; Wendland, Kerstin; Mellenthin, Lisa; Mackensen, Andreas; Müller, Fabian (Bioconjugate Chemistry, 2021)
Many proteins are still routinely expressed prokaryotically in Escherichia coli, some because they are toxic to eukaryotes. Immunotoxins, which are fusion proteins of a targeting moiety and a truncated Pseudomonas exotoxin A, kill target cells by arresting protein synthesis. Thus, immunotoxins must be expressed in E. coli. Proteins expressed in E. coli are contaminated by endotoxin (also called lipopolysaccharides (LPS)). LPS binds to toll-like receptors, inducing up to life-threatening systemic inflammation in mammals. Therefore, accepted LPS limits for therapeutics as well as for substances used in immunological studies in animals are very low. Here, we report the use of Triton X-114 and polyamine-based wash strategies, which only in combination achieved LPS-contamination well below FDA limits. Resulting LPS-reduced immunotoxins were purer and up to 2.4-fold more active in vitro. Increased activity was associated with a 2.4-fold increase in affinity on cell surface expressed target antigen. The combination method maintained enzymatic function, protein stability, and in vivo efficacy and was effective for Fab as well as dsFv formats. With some modifications, the principle of this novel combination may be applied to any chromatography-based purification process.
CRIS-Team Scopus Importer:2021-05-14